Cancer cell death using metabolic glycan labelling techniques. Issue 73 (1st September 2020) - Park, Sang-Hyun; Jung, Hyoje; Lee, Hosoowi; Kim, Tae Min; Cho, Jin Won; Jang, Woo-Dong; Hyun, Ji Young; Shin, Injae
Abstract : We report a method for selectively inducing cancer cell death that utilizes metabolic glycan labelling combined with ADCC or PDT. Abstract : Herein we describe a method for inducing cancer cell death, which relies on the use of a H2 O2 -responsive glycan metabolic precursor in conjunction with antibody-dependent cellular cytotoxicity (ADCC) or photodynamic therapy (PDT).